Implementasi strategi kolaboratif terhadap pencapaian hasil belajar fisika siswa di kelas X SMA - Putri Lenggogeni; Amali Putra (Universitas Negeri Padang, 2019)
In the 21st century, the ability to collaborate is one of the competencies to be achieved through learning. Therefore, that ability must be applied in schools. This study aims to determine the effect of the application of collaborative strategy in physics learning to the achievement of student learning outcomes in high school which was carried out in class X SMAN 12 Padang in the odd semester of the academic year 2019/2020. This research belongs to the Quasi Experiment Research with the Posttest Only Control Group Design. As the study population were all students of class X IPA SMAN 12 Padang. The sampling technique is Porposive Sampling followed by Cluster Random Sampling and obtained class X IPA 1 as an experimental class and class X IPA 2 as a control class. Research data in the form of student learning outcomes data obtained through instruments in the form of posttest on aspects of knowledge. The instrument used has fulfilled its validity and reliability through trials. The results showed that the posttest mean score of the experimental class was 68.82 higher than the posttest mean value of the control class that was 61.59. T test results at alpha level of 5% showed that the value of t count (4.09) > t table (1.99), so it was concluded that the difference in value was due to differences in treatment.